2018
DOI: 10.4103/ejd.ejd_307_17
|View full text |Cite
|
Sign up to set email alerts
|

Influence of light activation of simplified adhesives on the shear bond strength of resin cements to a leucite-reinforced ceramic

Abstract: Objective:This study aims to evaluate the influence of the light activation of simplified adhesives on the shear bond strength of resin cements to a glass-ceramic. Three factors were evaluated: (1) cement in two levels (light cured and dual cured); (2) adhesive in two levels (Single Bond 2 and Single Bond Universal), and (3) light activation in two levels (yes or no).Materials and Methods:Thirty-two 1-mm thick slices of a leucite-reinforced glass-ceramic (IPS Empress CAD) were divided into eight groups accordi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The higher the stress concentration in the load application area, the lower is the bond strength. Studies concluded that the use of a knife-edge chisel results in lower bond strength values than that of the wire loop, wherein the load is distributed over a larger area [ 84 ]. Moreover, it was found that the loading with stainless steel tape allowed more uniform stress distribution at the bond interface and was a more reliable way to evaluate the bond strength.…”
Section: Factors That Affect Bond Strength Measurementmentioning
confidence: 99%
“…The higher the stress concentration in the load application area, the lower is the bond strength. Studies concluded that the use of a knife-edge chisel results in lower bond strength values than that of the wire loop, wherein the load is distributed over a larger area [ 84 ]. Moreover, it was found that the loading with stainless steel tape allowed more uniform stress distribution at the bond interface and was a more reliable way to evaluate the bond strength.…”
Section: Factors That Affect Bond Strength Measurementmentioning
confidence: 99%
“…This can be explained by the greater cementation line in this group, which reduces the bond strength between GFPs and dentin. 12 In addition, some studies show that the use of simplified adhesive with dual cement does not show bond strength, 24 although the manufacture recommend the use and some studies shows the chemical incompatibility between the evaluated simplified adhesives and the dual-cured resin cement was not significant 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…This approach is interesting to improve the adaptation of the veneer to the dental structure. It has been shown that this type of conduct would not influence negatively on the final shear bond strength to a vitreous ceramic [18]. In the cementation, a resin-based lightactivated veneer cement was used.…”
Section: Discussionmentioning
confidence: 99%